Puzzling inefficiency of H5N1 influenza vaccines in Egyptian poultry - Kim, Jeong-Ki (National Academy of Sciences, 2010)
In Egypt, efforts to control highly pathogenic H5N1 avian influenza virus in poultry and in humans have failed despite increased biosecurity, quarantine, and vaccination at poultry farms. The ongoing circulation of HP H5N1 avian influenza in Egypt has caused >100 human infections and remains an unresolved threat to veterinary and public health. Here, we describe that the failure of commercially available H5 poultry vaccines in Egypt may be caused in part by the passive transfer of maternal H5N1 antibodies to chicks, inhibiting their immune response to vaccination. We propose that the induction of a protective immune response to H5N1 is suppressed for an extended period in young chickens. This issue, among others, must be resolved and additional steps must be taken before the outbreaks in Egypt can be controlled.